The conservation and signatures of lincRNAs in Marek’s disease of chicken - He, Yanghua (Sci Rep, 2015)
Long intergenic non-coding RNAs (lincRNAs) associated with a number of cancers and other diseases have been identified in mammals, but they are still formidable to be comprehensively identified and characterized. Marek’s disease (MD) is a T cell lymphoma of chickens induced by Marek’s disease virus (MDV). Here, we used a MD chicken model to develop a precise pipeline for identifying lincRNAs and to determine the roles of lincRNAs in T cell tumorigenesis. More than 1,000 lincRNA loci were identified in chicken bursa. Computational analyses demonstrated that lincRNAs are conserved among different species such as human, mouse and chicken. The putative lincRNAs were found to be associated with a wide range of biological functions including immune responses. Interestingly, we observed distinct lincRNA expression signatures in bursa between MD resistant and susceptible lines of chickens. One of the candidate lincRNAs, termed linc-satb1, was found to play a crucial role in MD immune response by regulating a nearby protein-coding gene SATB1. Thus, our results manifested that lincRNAs may exert considerable influence on MDV-induced T cell tumorigenesis and provide a rich resource for hypothesis-driven functional studies to reveal genetic mechanisms underlying susceptibility to tumorigenesis.